2011
DOI: 10.1108/17465721111175010
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of different sources of social support and civic participation with self‐rated health

Abstract: Purpose -Social support from different sources is beneficial for health and often helps individuals to cope with stress and illness. The aim of this paper is to simultaneously examine the effects of social support from personal, professional, and community networks and other factors in relation to health.Design/methodology/approach -A cross sectional postal and web-based survey was undertaken to examine these relationships in a random sample of 10,000 households in Wandsworth, London. Social support variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 47 publications
0
17
1
Order By: Relevance
“…The main aim of this study was to explore the associations between measures of social support from different domains and sources on the one hand and various health and work outcomes on the other. Although there is quite a lot of detailed evidence and research from outside Switzerland on such associations, and on the association between social support and health in particular, social supports from different sources and networks have rarely been studied simultaneously and compared directly with each other ( Jenkins and Elliott, 2004 , Van Daalen et al, 2006 , Van Woerden et al, 2011 ). Previous studies have either used measures of general social support or measures of support from a single source or a small number of sources.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main aim of this study was to explore the associations between measures of social support from different domains and sources on the one hand and various health and work outcomes on the other. Although there is quite a lot of detailed evidence and research from outside Switzerland on such associations, and on the association between social support and health in particular, social supports from different sources and networks have rarely been studied simultaneously and compared directly with each other ( Jenkins and Elliott, 2004 , Van Daalen et al, 2006 , Van Woerden et al, 2011 ). Previous studies have either used measures of general social support or measures of support from a single source or a small number of sources.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies suggest that social support is (directly) linked and (causally) related to health in general ( Holden et al, 2015 , Kumar et al, 2012 , Uchino et al, 2012 , Van Woerden et al, 2011 , Wright, 2006 ) and positively associated with physical health ( Barth et al, 2010 , Fiori and Jager, 2012 , Uchino, 2009 ), and with mental health in particular ( Kawachi and Berkman, 2001 , Plaisier et al, 2007 , Sinokki et al, 2010 , Sinokki et al, 2009 ). Previous studies and reviews also indicated that (perceived) social support even protects from cardiovascular disease and all-cause mortality ( Barth et al, 2010 , Brummett et al, 2005 , Uchino, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, employment is an indicator of socioeconomic position, so it is often associated with higher levels of neighbourhood cohesion. [187,251] Griffiths and colleagues showed that women who spent more time doing home duties had more contact with their neighbours. …”
Section: Discussionmentioning
confidence: 99%